O direito à saúde The right to health - Sueli Gandolfi Dallari (Universidade de São Paulo, 1988)
No fim do século XX a simples declaração de direitos não satisfaz ao povo. Busca-se delimitá-los determinando seu conteúdo, para se construírem estruturas que possam garantir o direito declarado. Nessa linha analisou-se a conceituação de saúde e de direito à saúde para procurar na organização do Brasil, Estado federal e capitalista, meios para garantir o direito à saúde. A municipalização das ações de saúde somada à necessidade de aprovação legislativa do Plano de Saúde e à organização judiciária local foram considerados elementos importantes para a efetivação do direito à saúde. At the end of the XXth century, a simple declaration of rights does not satisfy. It is necessary to establish its content meaning, and its limits with precision, so that the best structure to guarantee the right declared shall be created. Thus has tre conception of and the right to health been analysed with a view to descovering in the organization of Brazil - a federal and capitalistic State - the best tools effectively to guarantee the right to health. The municipalization of the Health Services, toghether with the need for the legislative approval of the Health Plan and the organization of the local judiciary, were considered important instruments in the quest to make the right to health effective.